The Implementation of Animated Video Media to Improve Analytical Skills in Islamic Religious Education - Yuyus Susilawati (UIN Sunan Gunung Djati Bandung, 2026)
Islamic Religious Education (PAI) is essential for responding to moral crises through the character building of the younger generation. However, the success of this process highly depends on the students' analytical skills, thus necessitating adequate learning innovations. This research utilizes a qualitative approach with a literature study method to examine the implementation of animated video media in improving students' analytical skills regarding PAI learning materials. The study shows that animated videos can present materials in a more engaging, interactive, and contextual manner. The use of this audio-visual media is proven to increase students' attention, motivation, and participation, thereby helping them analyze Islamic values more deeply. The implementation of animated videos serves as an effective pedagogical alternative in supporting the construction of students' knowledge. This improvement in analytical skills has become a crucial foundation for building strong character. Thus, animated videos function not only as a means of delivering material but also as an educative instrument for more meaningful PAI learning.